The Importance of Self-Acceptance and Gratitude as Mediators to Increase The Influence of Social Support on Subjective Well-Being in Parents of Children with Special Needs - Alice Zellawati; Dwi Yuwono Puji Sugiharto; Mulawarman Mulawarman; Sunawan Sunawan (Universitas PGRI Yogyakarta, 2026)
This study aims to analyze the role of self-acceptance and gratitude in mediating the influence of social support on subjective well-being. The research sample consisted of 102 mothers of children with special needs aged 1–12 years, selected through purposive sampling. The instruments used included the SWLS (Satisfaction with Life Scale) and PANAS (Positive Affect Negative Affect Schedule) to measure subjective well-being; GQ-6 (Gratitude Questionnaire) to assess gratitude; MSPSS (Multidimensional Scale of Perceived Social Support) to assess social support; and PPAS (Porter Parent Acceptance Scale) to assess self-acceptance. Data were analyzed using path analysis mediation with JASP version 18.3. Scientifically, this research contributes to expanding psychological understanding of internal and external factors that influence parental subjective well-being through positive emotional mechanisms. The findings show that self-acceptance and gratitude significantly mediate the effect of social support on subjective well-being, with a total contribution of 97.4%. Keywords: gratitude, social support, subjective well-being, self-acceptance